ENERGY TRANSFORMATION: ASSESSMENT OF URBAN LIGNOCELLULOSIC BIOMASS BIOFUELS VIA HYDROTHERMAL CARBONIZATION: A REVIEW - VÁSQUEZ LLANOS, SEGUNDO A. (2024)
URBAN LIGNOCELLULOSIC BIOMASS (ULB), DERIVED FROM THE MAINTENANCE OF PUBLIC AND PRIVATE GREEN SPACES, SUCH AS PARKS, GARDENS, SPORTS FACILITIES, AND AREAS ALONG ROADS, EMERGES AS A SOLID ALTERNATIVE TO REPLACE FOSSIL SOURCES. THESE RESOURCES STAND OUT DUE TO THEIR ABUNDANCE, LOW COST, AND AVAILABILITY. HYDROTHERMAL CARBONIZATION (HTC) EMERGED AS AN EFFICIENT TECHNOLOGY TO PROCESS THIS BIOMASS THAT HAS A HIGH MOISTURE AND ASH CONTENT, ELIMINATING THE NEED FOR PRIOR DRYING. THIS ARTICLE REVIEWS THE CONVERSION OF ULB TO SOLID BIOFUELS THROUGH THE HTC PROCESS, ADDRESSING THE PHYSICOCHEMICAL AND ENERGETIC PROPERTIES OF ULB AND THE RESULTING HYDROCHAR, AS WELL AS THE HTC PROCESS AND THE INFLUENCE OF THE OPERATING VARIABLES THAT AFFECT THE ENERGETIC QUALITY OF HYDROCHAR. THE CARBONIZATION TEMPERATURE (180 TO 280 °C) HAS A VERY SIGNIFICANT INFLUENCE MORE THAN THE RESIDENCE TIME (0.5 TO 24 H) ON THE INCREASE IN THE HIGHER HEATING VALUE (17.83 TO 30.12 MJ KG-1) AND THE FUEL RATIO, THE DECREASE IN THE H/C AND O/C RATIOS, THE DECREASE IN THE COMBUSTIBILITY INDEX, THE INCREASE IN THE IGNITABILITY INDEX (> 14.5 MJ KG-1), AND THE CARBON RANGE. HOWEVER, HIGH CARBONIZATION TEMPERATURES AND LONG RESIDENCE TIMES IN THE REACTOR ARE UNSUITABLE BECAUSE THEY REQUIRE LARGE AMOUNTS OF ENERGY TO PERFORM HTC. THEREFORE, BIOFUEL PRICES, BIOMASS LOGISTICS, OPTIMIZATION OF HTC PROCESS VARIABLES, AND REDUCTION OF ENERGY CONSUMPTION ARE CHALLENGES FOR THE HTC PROCESS TO GENERATE A SOLID BIOFUEL WITH EXCELLENT ENERGY PROPERTIES. © 2024, AIDIC SERVIZI S.R.L.